The impact of Pesticides and Workload on Osteoarthritis Incidence in Farmers: A Narrative Review - Lailatul Maghfiroh; Heni Fatmawati; Ika Rahmawati Sutejo (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2022)
An osteoarthritis is a group of pathologies in joints that include cartilage degradation, bone remodeling, osteophyte formation, and synovial inflammation which in turn can cause pain, stiffness, swelling, and loss of normal joint function. The increasing prevalence of osteoarthritis is associated with jobs that require physical strength (physically demanding) or heavy work, one of which is agriculture. This is in line with the World Health Organization's statement, farming for 1-9 years increases the risk of osteoarthritis 4.5 times. Besides, farming for 10 years or more increases the risk of osteoarthritis by 9.3 times. The purpose of this study was to determine the association between pesticide use and workload (which includes work attitude, working period, and heavylifting) and the incidence of osteoarthritis in farmers. This study uses a narrative review method on journals of the last 10 years. The results of this study indicate that pesticides are not associated with osteoarthritis, based on studies on osteoarthritis patients that show no difference in serum concentrations of organophosphate, pyrethroid, and nenonicotinoid pesticides and their metabolites. Conversely, work attitude and working period are associated with osteoarthritis in farmers. The work attitude associated with osteoarthritis especially knee osteoarthritis is the squatting and kneeling posture. Meanwhile, the heavylifting did not have a significant relationship with osteoarthritis, especially knee osteoarthritis among farmers. The conclusion of this study is there is no relationship between the use of pesticide and osteoarthritis. However, there is a relationship between work attitudes & working period and osteoarthritis in farmers.